Faktor-Faktor Penyebab Terjadinya Syndrome Dyspepsia Pada Remaja Putri - Habsari, Maharani Kusuma; Angraini, Dian Isti; Yuningrum, Hesti; Wardani, Dyah Wulan Sumekar Rengganis (CV. Jasa Sukses Abadi, 2024)
One of the most common non-communicable diseases is dyspepsia syndrome. A collection of symptoms in the upper gastrointestinal tract known as dyspepsia syndrome includes pain or discomfort in the upper abdominal area, a burning sensation in the chest, a feeling of fullness and early satiety, nausea, and vomiting. Indonesia ranks third after the United States as the country with the highest prevalence of dyspepsia syndrome, reaching 40–50%. Various risk factors, such as age, gender, dietary patterns, breakfast habits, consumption of spicy and sour foods, fast food, irritative beverages (soda, coffee, alcohol), exercise habits, smoking, nutritional status, and socioeconomic factors, can lead to the occurrence of dyspepsia syndrome. Adolescence is one of the risk factors that influence the occurrence of dyspepsia syndrome. Adolescents who are at higher risk of developing dyspepsia syndrome are those of the female gender. Teenage girls are more likely to pay attention to body shape and have a desire to emulate their online idols, which can lead them to adopt strict diets and irregular eating habits. Excessive physical activity contributes to the poor eating habits and breakfast habits of teenagers. The consumption of unhealthy foods, such as spicy and sharp-flavoured dishes, will increase stomach acid production. Stress in adolescents can be one of the triggers for dyspepsia syndrome. Prolonged stress can disrupt the digestive system and cause symptoms in healthy individuals. Every teenager with a busy schedule must be able to manage their time and schedule to avoid dyspepsia syndrome by bringing a packed lunch during activities.